PENGEMBANGAN E-LEARNING SYSTEM SD STRADA KARAWACI - Desanti, Ririn Ikana; Suryasari; Wella; Johan, Monika Evelin; Faza, Ahmad (FKIP UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2024)
Learning Management System (LMS) has become one of the media used to support online teaching learning activities. LMS has a wide range of functions such as administration, documentation, and reporting. The condition of the Covid-19 pandemic in 2020 has caused SD Strada Karawaci to find a way to keep providing school supplies to the students. The Information Systems Study Program – Universitas Multimedia Nusantara (IS-UMN) has a strong commitment to make a positive contribution to the community, one of which is through community service activities (PKM). IS- UMN organizes PKM activities with one of its goals to improve literacy of information technology of the community. In general, the activities of PKM IS-UMN are divided into two stages: system development and training. Therefore, in the first phase of the activities of PKM IS-UMN will design an e-learning system for elementary school of Strada Karawaci. The PKM team conducted in-depth research to understand the user needs (requirements) and conducted interviews with teachers and students. In addition, the development phase of the e-learning system is also carried out with consideration of the curriculum and school learning methods.